The Influence of Cooperative Learning Model Type Team Assisted Individualized of Interactive Media Assistance to Students' Mathematical Communication Ability - Yarmasi, Yarmasi; Fonna, Mutia; Mursalin, Mursalin (Universitas Malikussaleh, 2020)
Mathematics is a subject that must be mastered by every students because it relates to everyday life. However, many students consider mathematics to be a difficult and scary subject. Students only consider mathematics as a subject that includes numbers into the formula and the process of memorizing lessons. This results in low students' mathematical communication skills, especially in solving math tasks in the form of stories. This study aims to see the mathematical communication skills of students who are taught through the Team Assisted Individualized (TAI) type of cooperative learning model assisted by interactive media that is better than using scientific learning. The approach used in this research is quantitative. This research is a quasi experiment. The population of this study were all students of class VII and students of class VII 1 as the control class and class VII 3 as the experimental class. The samples were selected by purposive sampling. The research design used was the nonequivalent control group posttest-only design. Retrieval of data in the study using students' mathematical communication tests (posttest). Data collected from the results of the analysis test using SPSS 25 to find normality using the One-Sample Kolmogorov-Smirnov Test, and hypothesis testing using the Mann-Whitney U test. Regarding the research objectives, the results obtained from this study are students' mathematical communication skills. through cooperative learning type Team Assisted Individualized (TAI) assisted by interactive media gives an effect compared to students who get scientific learning. Based on the results of the Mann-Whitney U test, it is known that the Asymp value. Sig. (2-tailed), namely 0.001 <α 0.05.